Utopias possíveis: percursos do artista como agente transformador - Pereira, Davi Silva (2011)
The thesis is structured into three chapters. Due to the interlacement of thoughts it will be establish a dialogue among theories and practices of Joseph Beuys, Allan Kaprow and Andre Comte-Sponville. The German artist, from its construction in post- war, especially those that touch the expanded concept of art, social sculpture and the belief that we are all artists; the American artist, especially in considerations to their concerns about an-artist and the connection between art and life; and the French philosopher through his concepts about a possible range of happiness in the contemporary world. The ideas of these two artists- authors and researchers and the philosopher will lead investigations about how art and artist can be present in a possible transformation of society, from the contact with little movements of life and its social actors